IMPLEMENTASI MODEL PEMBELAJARAN PAI BERBASIS NILAI ISLAMI DALAM UPAYA MENINGKATKAN PEMAHAMAN KONSEPTUAL MAHASISWA DI UNIVERSITAS ISLAM MADURA - Supandi; Subhan, Mohammad; Khadavi, M. Jadid (LPPM STAI Muhammadiyah Probolinggo, 2024)
The implementation of the PAI learning model based on Islamic values to increase students conceptual understanding at UIM needs to be researched and explored scientifically, considering that PAI is the foundation of Islamic education to produce graduates who are by the Islamic management of the UIM Institution and have the ahlussunnah waljamaah bent. However, in reality, phenomena are presented that are often not by Islamic rules and teachings, this is the reason why this research is necessary to carry out this research. While the research approach used is qualitative phenomenological, the data sources in this research are UIM residents taken randomly by researchers such as students, lecturers, and employees. The validity of the data is to convince the researcher that the data obtained is valid, the researcher uses the concept of triangulation. The research results show that the Islamic Values-Based PAI Learning Model is carried out holistically in the learning process, which does not only focus on conceptual understanding and material but also on students themselves and the application of Islamic values in real life. Meanwhile, the impact of students' conceptual understanding has a positive impact on religious concepts and the ability to relate these concepts to the context of everyday life. Meanwhile, intensive interaction between lecturers and students as well as space for discussion and reflection in the learning process makes a significant contribution to the effectiveness of the Islamic Values-based PAI education and learning model. The implementation of the PAI learning model based on Islamic values can be used as a reference for lecturers and curriculum managers to improve the quality of Islamic religious education at the Islamic higher education level. Keywords: Learning Model; Islamic Values; Conceptual Understanding.